Antibacterial Activity of Seligi Leaf Extracts and Fractions against Pseudomonas Aeruginosa and Staphylococcus Aureus Bacteria and Their Bioautography - Prastika, Rizky Wanda; Muflihah, Cita Hanif (Newinera Publisher, 2024)
Seligi leaf (Phyllanthus buxifolius muell. Arg) is one of the medicinal plants that are traditionally used by the community. This plant can empirically treat several diseases, thanks to the content of antibacterial compounds such as flavonoids and terpenoids. The bacteria Pseudomonas aeruginosa and Staphylococcus aureus are the main causes of nosocomial infections. The purpose of this study is to examine the antibacterial activity of seligi leaf extract and fraction against Pseudomonas aeruginosa and Staphylococcus aureus bacteria, as well as to identify active compounds that have an important role in these antibacterial activities. The extraction process is carried out using the maceration method with 70% ethanol. The antibacterial activity test was carried out by the disc diffusion method, with concentration of 20, 40, 60, 80, and 100% for extraction, then for all fractions a concentration of 50 %. The test results showed that the extract had antibacterial activity against Staphylococcus aureus on 8 mg/disk loading disk with inhibition zone diameters of 10.33 ± 0.58 mm and 12.16 ± 1.41 mm, but no inhibition zones formed against Pseudomonas aeruginosa on all loading disks. The identification of compounds in seligi leaves using the KLT method showed that the extract contained phenolics, flavonoids, and terpenoids, while the ethyl acetate fraction contained phenolics and alkaloids. However, bioautographic tests do not indicate any antibacterial potential.